Avaliação do Programa de Transferência da Gestão em Perímetros Públicos de Irrigação: o caso de Morada Nova - Albuquerque, José Alfredo de (2008)
This study focuses on the reflective analysis on the process of transferring the management of the Irrigated Perimeter Morada Nova in the period between 2004 and 2007, when it occurs in the implementation of Plan Plurianual of the Federal Government for the 2004-2007 quadrennium. It is in this Plan Plurianual which the Program 1038 - Transfer of Public Management of the Lengths of Irrigation, establishing guidelines for transfer, ultimately, the management of the government to users of the irrigation system. The methodology used in this study involved a literature search and a documentary, including field research involving irrigating of the Perimeter Irrigated Morada Nova, to represent a mirror of all perimeters implanted in the decade of seventy, and consultation with official documents, complemented with technical reports . The study could understand that the process of transferring advanced management in the recovery of infrastructure, but no longer want to work for an appropriation of methodological techniques of this process with the community of users of the irrigation system. This study has also, identify the significant exception of not irrigating the participation and involvement in the process of transfer of management.